HALAL AWARENESS OF THE ZILLENNIAL GENERATION ON PURCHASING DECISIONS FOR HALAL PRODUCTS MEDIATED BY PURCHASING INTEREST - Putriana, Putriana (Jurnal Al-Iqtishad, 2024)
The Ziennial generation is one of the consumers who are the target market in marketing goods for producers. The millennial generation's consumption behavior is still unstable, easily influenced by what they see and hear. Based on this, the aim of this research is to analyze the influence of halal awareness on purchasing decisions for halal products which is mediated by purchase interest. The methodology used in this research is quantitative with the SEM-Smart PLS analysis tool. The research was conducted on 100 people from the millennial generation using a random sampling procedure. The research results show that there is a significant positive influence of halal awareness on purchasing decisions, there is a significant positive influence of halal awareness on purchasing interest, there is a significant positive influence of interest on purchasing decisions and there is a significant positive influence of halal awareness on purchasing decisions through purchasing interest. Theoretically, halal awareness must be used as a theoretical basis and measure in product purchasing decisions and practically it is hoped that the millennial generation will increase their understanding and knowledge about halal products such as raw materials and product manufacturing processes and are obliged to buy and use halal products.